2021
DOI: 10.1186/s12902-021-00800-y
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Caveolin-1 (rs3807992) polymorphism and major dietary patterns on cardio-metabolic risk factors among obese and overweight women

Abstract: Background Caveolin-1 (CAV-1) is a cholesterol-dependent essential component located in caveolae. Several studies have been CAV-1 related to cardio-metabolic parameters in animal models, however, there are few studies in humans. Importantly, there is no study has investigated the interaction between CAV-1 rs3807992 gene and dietary patterns (DPs) on cardio-metabolic risk factors. Methods The current cross-sectional study was conducted on 404 overwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 43 publications
3
25
0
Order By: Relevance
“…Beside, the lower liver enzyme in A-allele carriers following an hPDI in the present study can be dependent on the caffeine intake during the hPDI. In this term, we previously found a decreased AST in A-allele carriers who consumed more caffeine in a healthy dietary pattern 45 .Interestingly, a candidate gene for the favorable impact of caffeine consumption is located near the CAV-1 gene 75 , Therefor, we suggested a possible interaction between caffeine and CAV-1, which we hope will be confirmed in future study.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Beside, the lower liver enzyme in A-allele carriers following an hPDI in the present study can be dependent on the caffeine intake during the hPDI. In this term, we previously found a decreased AST in A-allele carriers who consumed more caffeine in a healthy dietary pattern 45 .Interestingly, a candidate gene for the favorable impact of caffeine consumption is located near the CAV-1 gene 75 , Therefor, we suggested a possible interaction between caffeine and CAV-1, which we hope will be confirmed in future study.…”
Section: Discussionsupporting
confidence: 52%
“…Serum insulin level was also measured by radioimmune assay. More detailed about biochemical measuring are reported in our previous study 45 .…”
Section: Methodsmentioning
confidence: 99%
“…It was observed that a genetic variant of CAV-1 (rs3807992) was associated with increased MetS risk, which is consistent with previous studies that revealed a significant association between the minor allele in CAV-1 variations and the odds of metabolic diseases (10,11,15,17) . Previous studies by our research team have shown association between CAV-1 rs3807992 and metabolic disease (21,22) . Also, compared with other candidate gene studies, no studies had evaluated SNP rs3807992 and MetS risk.…”
Section: Discussionmentioning
confidence: 66%
“…Another study examined the main role of the CAV1 gene in developing the cardiovascular disease with an effect on lipid factors and reported significant associations [ 14 ]. In this regard, we recently explored information about the interaction between CAV1 and dietary intake in overweight and obese women [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%